Low-energy and area-efficient tri-level switching scheme for SAR ADC - Yuan, C. (2013)
A novel low-energy tri-level switching scheme for low-power successive approximation register (SAR) ADC is proposed. With the input common-mode voltage (Vcm) designed to be exactly half of the reference voltage (Vref ), the switching energy of the proposed switching scheme is reduced by 96.89% as compared with the conventional architecture. Besides the large energy saving, the proposed switching scheme also reduces the number of capacitors in the ADC capacitor array by 75%, which in turn results in an area-efficient SAR ADC.